Coaching and Mentoring of Corporate Culture in Efforts to Improve TDW Group Performance - Hojanto, Ongky; Kasmir, Kasmir (Dinasti International Journal of Digital Business Management, 2022)
This study aims to obtain some information regarding the performance improvement that has occurred in the TDW Group, especially several business units due to the organizational culture formed through the coaching and mentoring process through case studies. The paradigm in this study uses Post-Positivism which is naturalistic. The data analysis performed is inductive based on the facts determined. This research was conducted at TDW Group which has 11 business units. The selection of informants in this study used a purposive sampling technique. The sampling technique used is purposive sampling, with data collection through; interviews, literature studies, and observation. Data analysis in this study used interactive model data analysis techniques, assisted by the NVivo 12 plus software. Tung Desem Waringin made the coaching and mentoring process gain interest for participants to participate in the process. Coaching and mentoring with the title Friday with TDW can instill a corporate culture Juni Bawa Tali (Jujur, Nilai Tambah, Tanggung Gugat dan Lingkaran Malaikat) so that it is well remembered and understood by staff from several business units. Finally, there is the influence of the implementation of corporate culture on employee performance, which can personally increase employee productivity.